2007
DOI: 10.1002/cne.21298
|View full text |Cite
|
Sign up to set email alerts
|

Two types of Drosophila R7 photoreceptor cells are arranged randomly: A model for stochastic cell‐fate determination

Abstract: The R7 photoreceptor cells of the Drosophila retina are ultraviolet sensitive and are thought to mediate color discrimination and polarized light detection. In addition, there is growing evidence that the color sensitivity of the R8 cell within an individual ommatidium is regulated by a genetic switch that depends on the type of R7 cell adjacent to it. Here we examine the organization of the two major types of R7 cells by three different rigorous statistical methods and present evidence that they are arranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 65 publications
3
50
0
Order By: Relevance
“…For example, during fruit fly eye development, precursor cells in a specific area of the eye differentiate into cells with two types of photoreceptor and maintain their cell fate. It has also been reported that the differentiation of these photoreceptors is purely stochastic and independent (11). Recent studies (12,13) have identified a mutual inhibitory gene regulation motif as the core system driving the stochastic differentiation, but the exact mechanism of the stochastic differentiation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during fruit fly eye development, precursor cells in a specific area of the eye differentiate into cells with two types of photoreceptor and maintain their cell fate. It has also been reported that the differentiation of these photoreceptors is purely stochastic and independent (11). Recent studies (12,13) have identified a mutual inhibitory gene regulation motif as the core system driving the stochastic differentiation, but the exact mechanism of the stochastic differentiation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Few mechanisms, however, have been proposed to explain the scenario of random and yet irreversible cell fate determination, which is commonly seen in development and cell differentiation. Recent studies (11)(12)(13) show examples of stochastic and irreversible cell differentiation in multicellular organisms, and they have identified that the central regulatory motif driving these stochastic differentiations is a mutual inhibitory gene regulatory network (GRN), a common topological module that can generate bistability. However, with neither fluctuating environmental cues nor spontaneous state transitioning identified in these cases, an understanding of how cells differentiate stochastically and irreversibly into distinct subpopulations remains elusive, especially when under the tight control of GRNs.…”
mentioning
confidence: 99%
“…In the ommatidia of the "pale" type, the R7 cell expresses the Rh3 opsin, which is most sensitive to ultraviolet (UV) light, while R8 expresses the Rh5 opsin, sensitive in the blue; whereas in "yellow" ommatidia, the R7 cell expresses the long-UV sensitive Rh4 opsin and the underlying R8 expresses the green-sensitive Rh6 opsin. The two types pattern the eye randomly (Bell et al, 2007) and presumably extend the spectral range of the retina (Morante and Desplan, 2008). Both R7 and R8 are required functionally to enable spectral preference and color vision (Gao et al, 2008;Schnaitmann et al, 2010Schnaitmann et al, , 2013Yamaguchi et al, 2010;Melnattur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1C) (Chou et al, 1996;Chou et al, 1999;Papatsenko et al, 1997). p/y subsets comprise the majority of ommatidia and are randomly distributed throughout the retina in a 30:70 (p:y) ratio (Bell et al, 2007;Kirschfeld and Franceschini, 1977;Stark and Thomas, 2004). DRA ommatidia are two specialized rows of ommatidia that express the same opsin, Rh3, in both R7 and R8 PRs, form distinct polarizing rhabdomeres, and interpret the e-vector of polarized light (Fig.…”
Section: Introductionmentioning
confidence: 99%